Behavior of drag anchor under uni-directional loading and combined loading. (1st January 2017) - Wu, Xiaoni; Chow, Yean Khow; Leung, Chun Fai
Abstract: Drag anchor is an economical foundation option for offshore floating structures. Although there are studies on ultimate pullout capacity of drag anchors, the drag-in installation process is still not fully understood. The approach using yield envelopes for drag anchor under combined loading for the installation behavior prediction is promising. However, more needs to be done to understand anchor bearing behavior during the installation process. The current study focuses on the capacity of drag anchor under uni-directional vertical, horizontal and moment loading in uniform clay and the behavior of anchor fluke under combined loading. Finite element analyses are conducted for "wished-in-place" anchor fluke. The effect of anchor embedment depth and soil overburden pressure is investigated. The horizontal and rotational capacity factors for different embedment ratios and overburden pressure ratios, which have not been covered in the existing studies on anchor capacity, are provided here. The effect of anchor/soil interface breakaway condition on the capacity under the three uni-directional loading is also studied. Based on the understanding of drag anchor capacity under uni-directional loading, its behavior under combined loading is characterized by the yield envelopes for both shallow and deep anchor behavior. The current study provides a good understanding for the capacity of drag anchors. The yield envelopes can be used for the prediction of anchor trajectory with consideration of both shallow and deep anchor behavior. Highlights: A comprehensive study of drag anchor capacity under uni-directional vertical, horizontal and rotational loadings. The effect of anchor embedment depth and soil overburden pressure ratio on the capacity and anchor failure mechanism. The influence of anchor breakaway condition on the capacity and the recommendation for numerical study consideration. The yield envelopes under combined loading for deep and shallow anchor behavior with rough and smooth interface conditions.